Respuesta :
Answer:
Part a) [tex]x^{2}+4x+4[/tex]
Part b) [tex]x^{2}-10x+25[/tex]
Step-by-step explanation:
we know that
A perfect square trinomial is equal to
[tex](x+a)^{2} =x^{2}+2ax+a^{2}[/tex]
Part a) we have
[tex]x^{2}+4x[/tex]
Compare with the formula of a perfect square trinomial
[tex]x^{2}+4x=x^{2}+2ax+a^{2}[/tex]
so
[tex]4x=2ax[/tex]
[tex]4=2a[/tex]
[tex]a=2[/tex]
therefore
[tex](x+a)^{2} =(x+2)^{2}=x^{2}+4x+4[/tex]
Part b) we have
[tex]x^{2}-10x[/tex]
Compare with the formula of a perfect square trinomial
[tex]x^{2}-10x=x^{2}+2ax+a^{2}[/tex]
so
[tex]-10x=2ax[/tex]
[tex]-10=2a[/tex]
[tex]a=-5[/tex]
therefore
[tex](x+a)^{2} =(x-5)^{2}=x^{2}-10x+25[/tex]
The values are needed to make each expression a perfect square trinomial x^2 + 4x + 4 and x^2 – 10x + 25.
What is a perfect square?
A perfect square is a number system that can be expressed as the
square of a given number from the same system.
A. [tex]x^{2} +4x+4[/tex]
A perfect square trinomial is
[tex](x+a)^2 = x^2 + 2ax + a^2[/tex]
Compare with the formula of a perfect square trinomial
4x = 2ax
4 = 2a
a = 2
Therefore, [tex](x+a)^2 = (x+2)^2 = x^{2} +4x+4[/tex]
B. [tex]x^{2} -10x + 25[/tex]
A perfect square trinomial is
[tex](x+a)^2 = x^2 + 2ax + a^2[/tex]
Compare with the formula of a perfect square trinomial
-10x = 2ax
-10 = 2a
a = -5
Therefore, [tex](x+a)^2 = (x-5)^2 = x^{2} -10x+25[/tex].
Learn more about a perfect square;
https://brainly.com/question/385286
#SPJ3